Perkembangan Kognitif Siswa Kelas Rendah Sekolah Dasar Melalui Model PBL - Ulyawati, Ulyawati; Hotimah, Hotimah (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2025)
The purpose of this study was to find out the cognitive development of low-grade students and an overview of the cognitive development of low-grade students through the use of the PBL model. As for the research method, use literature review. Then the selection of relevant articles based on several databases such as indexed Google Scholar and Taylor &Francis, as well as articles entered maximum 10 years ago. The selection of articles in this study as many as 16 writings, including national articles 13 writings and international articles 3 writings in the priode June-July 2021. The results of the study, showed based on the age range of low-grade elementary school students are at 7-9 years that has entered concrete operations. The PBL is described as an ideology directed at the tradition of experience, where actual development is determined by self-solving and the level of potential development is determined through problem solving under the guidance of adults or in collaboration with more capable peers. Based on 8 national articles obtained related to the use of PBL learning models in developing low-grade students' cognitive, showing students' cognitive development during learning with the dominant PBL model shows changes in learning outcomes, critical thinking skills, problem solving, and process skills.